Endogenous glutathione biosynthesis and GsiB-dependent glutathione uptake contribute to oxidative stress resistance in Vibrio alginolyticus - Liting Xu; Maowang Jiang; Ruibing Peng; Xiamin Jiang; Qingxi Han; Weiwei Zhang (Journal of Invertebrate Pathology, 2026)

Screening nutrient sources to enhance biomass and eicosapentaenoic acid (EPA) production in the diatom Chaetoceros lorenzianus - Yijia Zhang; Ruibing Peng; Jiongming Zhang; Maowang Jiang; Xiamin Jiang; Jiayi Sun; Guoquan Zeng (Journal of Applied Phycology, 2026)

Evaluation of sodium hypochlorite toxicity on the early life stages of Pharaoh cuttlefish (Sepia pharaonis): Hatching, growth performance, and physiological stress responses - Zhongyin Zhang; Qi Niu; Huazheng Zhan; Ruibing Peng; Xiamin Jiang; Sheng Li; Maowang Jiang (Aquaculture, 2026)

Effects of nitrogen, phosphorus, iron, and silicon on the growth, total lipid content, and fatty acid composition of the diatom Corethron sp. - Maoyingzang Peng; Pingping Liu; Ruibing Peng; Xiamin Jiang; Sheng Li; Maowang Jiang (Journal of Applied Phycology, 2026)

Lipid-mediated photoprotection confers strong light resilience in hyperaccumulator Sedum alfredii - Yanjiao Dai; Jin Chen; Yang Mao; Huidan Jiang; Wenwen Zhao; Jing Peng; Ruibing Li; Ying Wang; Purui Guo; Mengnan Zhang; Chao Zhang; Jiaming Li; et al. (Plant Science, 2025)

Evaluation of different microalgal diets on feeding efficiency, growth performance, proximate composition, fatty acid composition, and digestive enzyme activities in juvenile Manila clam (Ruditapes philippinarum) - Jiayi Sun; Xu Chen; Yushun Lu; Jiahuan Wang; Jiongming Zhang; Guoquan Zeng; Xiamin Jiang; Ruibing Peng (Aquaculture International, 2025)

Hematological metabolic characteristics and dynamic regulation of free amino acids in muscle and ink in response to inkjet-induced stress in Sepia pharaonis - Ao Meng; Wencheng Xiao; Ruibing Peng; Xiamin Jiang; Qingxi Han; Sheng Li; Maowang Jiang (Aquaculture International, 2025)

Supramolecular host-guest interactions guided rapid biomineralization for blockade therapy of osteosarcoma - Beibei Xie; Yuanfu Ding; Ziyi Wang; Shengke Li; Yan Wang; Ruibing Wang; Shaowei Wang; Peng Li (Chemical Engineering Journal, 2025)

Characterization of ColA as a virulence factor of Vibrio alginolyticus H1 pathogenic to cuttlefish Sepia pharaonis - Haijuan Dai; Weibo Shi; Ya Li; Ruibing Peng; Maowang Jiang; Xiamin Jiang; Weiwei Zhang; Huajun Zhang; Qingxi Han (Aquaculture, 2025)

Multi-omics analysis reveals the toxic mechanism of tributyltin exposure causing digestive gland oxidative stress in cuttlefish (Sepia pharaonis) - Maowang Jiang; Maoyingzang Peng; Ao Meng; Weixia Zhang; Huilai Shi; Qingxi Han; Ruibing Peng; Xiamin Jiang (Journal of Hazardous Materials, 2025)

Effects of phosphorus sources on the growth, chlorophyll a and total lipids production, and fatty acids composition in Chaetoceros lorenzianus - Jinping Zhang; Xinyi Xia; Jiayu Wang; Xu Chen; Jiamei Li; Guoquan Zeng; Xuemei Duan; Qingxi Han; Ruibing Peng (Journal of Applied Phycology, 2025)

Effects of tank color on the growth performance, energy metabolism, and immunity of juvenile pharaoh cuttlefish, Sepia pharaonis - Jiawen Yu; Qilong Huang; Huan Chen; Xu Chen; Maowang Jiang; Qingxi Han; Xiamin Jiang; Ruibing Peng (Aquaculture, 2025)

Study on biological zero and effective accumulated temperature of embryonic development and gonadal development of cuttlefish Sepia pharaonis - Huan Zeng; Wencheng Xiao; Xiamin Jiang; Qingxi Han; Ruibing Peng; Sheng Li; Maowang Jiang (Molluscan Research, 2024)

Effects of light quality on the growth, productivity, fucoxanthin accumulation, and fatty acid composition of Thalassiosira pseudonana - Maoyingzang Peng; Shiyu Lin; Yinghan Shen; Ruibing Peng; Sheng Li; Xiamin Jiang; Maowang Jiang (Journal of Applied Phycology, 2024)

Metabolic perturbations and bacterial communities dysbiosis associated with skin ulcer disease progression in Sepia pharaonis - Liting Xu; Maowang Jiang; Ruibing Peng; Xiamin Jiang; Sheng Li; Weiwei Zhang; Qingxi Han (Aquaculture, 2024)

Effects of iron on the growth, chlorophyll a, total lipids, and fatty acids of Chaetoceros lorenzianus - Zuhao Zhang; Ruibing Peng; Xinyi Xia; Pingping Liu; Si Chen; Ran Xia; Xiamin Jiang; Maowang Jiang; Jianyuan Lin (Journal of Applied Phycology, 2023)

Succession of bacterial communities during a disease progress in cuttlefish Sepia pharaonis - Liting Xu; Yilong Ruan; Maowang Jiang; Ruibing Peng; Xiamin Jiang; Weiwei Zhang; Qingxi Han (Aquaculture International, 2023)

Effects of feed transition on digestive tract digestive enzyme, morphology and intestinal community in cuttlefish (Sepia pharaonis) - Maowang Jiang; Wencheng Xiao; Jingtao Ye; Liting Xu; Ruibing Peng; Qingxi Han; Zhenming Lü; Huilai Shi; Xiamin Jiang (Frontiers in Marine Science, 2022)
Sepia pharaonis is an excellent candidate for aquaculture in China. However, the low survival rate during early feed transition is a bottleneck restricting industrial development. Understanding the changes in digestive physiology and intestinal microflora during feed transition should enable us to meet their nutritional needs to improve production. In this study, we investigate the digestive enzyme of S. pharaonis and undertake histological observations of the digestive gland and intestine. The intestinal microflora 16S rRNA genes were also analyzed using high-throughput sequencing of the pre, mid, and post-feed transition stages (20, 40, and 60 days post-hatching (DPH), respectively). The digestive enzymes from the digestive gland (trypsin and chymotrypsin) rapidly decrease at 40 DPH when compared to their levels at 20 DPH, but mostly recovered by 60 DPH. The alkaline phosphatase and lipase increased sharply by 40 DPH, then peaked at 60 DPH. The intestinal digestive enzymes followed similar trends during feed transition, except for lipase activity, which decreased after 20 DPH and remained low, even at 60 DPH. Feed transition affects the morphogenesis of the digestive tract and feed transition stress leads to the impairment of the digestive gland and intestinal morphology, which reduces the digestive capacity, but almost totally recovers by 60 DPH. Moreover, the comparison of the intestinal microbial composition during feed transition revealed that the dominant phylum Bacteroidetes gradually increased to a peak at 40 DPH and then decreased until 60 DPH. The microbial composition changed with the most abundant genus Pseudomonas being replaced by Acinetobacter . The phylum and family level investigation suggested the microbiota in the rearing water had limited influence on the intestinal microbiota. The intestinal microbiota diversity increased during feed transition. This study improves our understanding of changes and adaptations in cuttlefish during feed transition.

Changes in embryonic development, juvenile growth and physiological adaptation of the cuttlefish Sepia pharaonis in response to photoperiod manipulation - Maowang Jiang; Huan Chen; Shuangnan Zhou; Qingxi Han; Ruibing Peng; Xiamin Jiang (Journal of Oceanology and Limnology, 2022)

Effects of Different Weaning Protocols on Survival, Growth and Nutritional Composition of Pharaoh Cuttlefish (Sepia pharaonis) Juvenile - Maowang Jiang; Ziru Han; Peng Sheng; Ruibing Peng; Qingxi Han; Xiamin Jiang (Journal of Ocean University of China, 2020)

Effects of temperature on the growth and microstructure formation of cuttlebone from cuttlefish Sepia pharaonis - Maowang Jiang; Ruibing Peng; Qingxi Han; Xiamin Jiang (Molluscan Research, 2020)

Effect of light intensity on embryonic development of the cuttlefish Sepia lycidas - Ruibing Peng; Xia-Min Jiang; Maowang Jiang; Sihan Chen (Aquaculture International, 2019)

Co-expressing GP5 and M proteins under different promoters in recombinant modified vaccinia virus ankara (rMVA)-based vaccine vector enhanced the humoral and cellular immune responses of porcine reproductive and respiratory syndrome virus (PRRSV) - Qisheng Zheng; Desheng Chen; Peng Li; Zhixiang Bi; Ruibing Cao; Bin Zhou; Puyan Chen (Virus Genes, 2007)